Praktikum Moda Hybrid Android Interface Untuk Mengembangkan Keterampilan Proses Sains Siswa - Deri Adiyanto; Riandi Riandi; Rini Solihat (Jurnal Penelitian Pendidikan IPA, 2024)
Science Process Skills are abilities that students must possess because they are applicable not only to science learning but also to daily life. To be familiar with scientific method activities, students must have direct experience in order to be trained in Science Process Skills. This study aims to enhance students' Science Process Skills through hybrid android interface mode practicum learning. The research data was collected using description questions previously validated by subject matter experts. This study conducted quasi-experiments using the Nonquivalent (pretest-posttest) Control Group Design method. The research participants included control and experimental groups. The research results show an increase in Science Process Skills in the experiment class as evidenced by the achievement of aspects of observation 71.25%, interpretation 78.25%, classification 86.12%, prediction 84.45%, conducting experiments or investigations 83.34%, communicating 63.33%, hypothesizing 79.63%, applying concepts 88.34%, and asking questions 82.43%. It shows that the practicum mode of the hybrid Android interface can develop Science Process Skills